A simple latex slide test for rheumatoid arthritis using the gamma globulin in the patient's serum. Issue 5 (September 1962) - Bird, R.; Burr, R. G.
Abstract : A latex slide test is described which is suitable for handling large numbers of specimens. The buffered latex suspension used is easily prepared from stable stock solutions at relatively low cost. It is not necessary to add Cohn fraction II (γ globulin) to the latex reagent. A comparison has been made with the sheep cell agglutination (Rose-Waaler) test in 508 cases and a 96% overall agreement obtained. Factors influencing the test have been investigated.